2021
DOI: 10.1108/sajm-03-2021-0028
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19 is driving fear and greed in consumer behaviour and purchase pattern

Abstract: PurposeThis research aims to study the recent changes in consumer behaviour and purchase pattern during the Covid-19 pandemic. Covid-19 pandemic has forced consumers to stockpile, which has its own consequences. The article proposes the importance of “minimalism in consumption” to avoid greed in consumer behaviour.Design/methodology/approachThe data are collected from consumers across India using an online survey during the first lockdown from March 2020 to May 2020. A simple random sampling technique is used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 43 publications
0
23
0
Order By: Relevance
“…The SOR theory postulates that a stimulus event causes an emotional reaction, which subsequently induces a behavioral response. Furthermore, recent evidence has demonstrated that consumers' decision-making and purchasing behavior are significantly correlated to the extent of fear and greed emotions as a consequence of COVID-19 [21]. In a similar vein, Yan et al [53] validated the role of psychological or emotional state in determining the effect of a stimulus on consumer behavior of either selection or rejection.…”
Section: Moderating Influence Of Travel Fomomentioning
confidence: 97%
See 2 more Smart Citations
“…The SOR theory postulates that a stimulus event causes an emotional reaction, which subsequently induces a behavioral response. Furthermore, recent evidence has demonstrated that consumers' decision-making and purchasing behavior are significantly correlated to the extent of fear and greed emotions as a consequence of COVID-19 [21]. In a similar vein, Yan et al [53] validated the role of psychological or emotional state in determining the effect of a stimulus on consumer behavior of either selection or rejection.…”
Section: Moderating Influence Of Travel Fomomentioning
confidence: 97%
“…Destination crisis marketing in an influential moderating mechanism can also be theoretically explained by the psychological reactance theory [54], which highlights the consumption behaviors and purchasing patterns in uncertain (e.g., COVID-19) conditions [21]. According to the psychological reactance theory, the consumers will continue their firstchoice behaviors if they feel the freedom of decision-making, whereas they will intend to do the opposite if they perceive threats to their freedom of choice [55].…”
Section: Moderating Effects Of Destination Crisis Marketingmentioning
confidence: 99%
See 1 more Smart Citation
“…People started to store essential products like pasta, noodles, oil, sugar, flour, napkins, toilet paper, surgical mask, yeast etc. Due to the anxiety of unobtainability (Satish, Venkatesh, & Manivannan, 2021) of such products people has formed a habit of buying extra amount of food and drinks that they don't even need that much. To some extent this has created shortage of some daily essentials in the market with substantial price hike of regular commodities.…”
Section: Increased Stockpilingmentioning
confidence: 99%
“…Some other reviews warn us about the general patterns that consumers have been producing since the covid-19 pandemic began. These include attitudes and habits such as spending or purchasing patterns (Di Crosta et al, 2021;Satish et al, 2021).…”
Section: Consumer Behavior and Covid-19 Literaturementioning
confidence: 99%